EVALUATION OF CORPUS LINGUISTICS AS A FIELD (Ustozlar uchun, 2025)
Corpus linguistics has transformed significantly from a marginal analytical tool into a central methodology within modern linguistic research. This study evaluates corpus linguistics as a field by examining its historical development, methodological foundations, applications, strengths, and limitations. Using a descriptive-analytical approach, the article synthesizes existing scholarly discussions and highlights the increasing relevance of corpus-based research in areas such as lexicography, language teaching, discourse analysis, and natural language processing. The evaluation demonstrates that corpus linguistics offers high empirical reliability, replicability, and analytical precision, despite persisting challenges related to representativeness, spoken data availability, and technical complexity. The findings suggest that corpus linguistics will remain a leading research paradigm due to its interdisciplinary applications and technological adaptability.